Diseño de un programa de recreación deportiva que promueva la inclusión y mejore la calidad de vida en los adultos mayores de la unión nacional de educadores jubilados núcleo de Cotopaxi en el año 2012-2013 - Iglesia Cruz, Diana del Pilar (2013)
The present research have as purpose create awareness among authorities of turn, through them transmit to the actors of this institution the importance what have the recreational activities and the benefits which will been gotten when are applied through Physical Sports Activity, recreation to use the sports practice, reach to foregroundwhat this will serve as a teaching-learning tool for the members of this important institution.The problem arisesbecause this institutionthe objectofstudy has notbeen given the importance tothephysical, recreationalsports activities; neither,they are not provided of professionalin the areaPhysical Culture, thereby promoting this activity in thehumanmembers ofthis cluster.The constructionof the theoretical frameworkand the developmentof the methodology arebasedon the principles ofcritical education. Themethodology that usedthisresearch workwas madethroughthe technique survey, which will allowed reachacceptable reliability, and will beassessed usingthe statisticsto meet theobjectivesof the questionsandthe theoretical framework, the alternative proposalof research contain: introduction, rationale, objectives.Sports activities area basic need thatwill serve as asupporting documentforseniors of the UNEJNC, allowing them toimprove their qualityof life throughprocedures, methodologies, strategies foran effectiveand efficientbenefitto participantsof the Institutionin search of betterdaysfor this sectorof societyand especially toencouragethe practice ofphysical sports activitiesin search of abetter andlongerlif.